1998
DOI: 10.1016/s0022-5347(01)63918-1
|View full text |Cite
|
Sign up to set email alerts
|

Renal Colic During Pregnancy: A Case for Conservative Treatment

Abstract: Renal colic in pregnant patients can be complicated by pyelonephritis and premature labor, especially if misdiagnosed or inadequately treated. Ultrasound is a safe and sensitive diagnostic test. Approximately two-thirds of renal calculi will pass spontaneously. For those who require intervention, placement of a Double-J stent is a safe and effective option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 12 publications
3
69
0
8
Order By: Relevance
“…2 It was estimated that there is one case of urolithiasis requiring active treatment in every 1500 pregnancies. 9 Fifty to 80% of stones during pregnancy pass spontaneously with conservative treatment 4 but, 20% to 30% of cases will need some form of active treatment such as placing a percutaneous nephrostomy (PCN) tube or performing ureteroscopic procedures. 10 The purpose of the treatment is to diminish maternal pain, to prevent renal dysfunction and urinary tract infection and to decrease obstetric complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 It was estimated that there is one case of urolithiasis requiring active treatment in every 1500 pregnancies. 9 Fifty to 80% of stones during pregnancy pass spontaneously with conservative treatment 4 but, 20% to 30% of cases will need some form of active treatment such as placing a percutaneous nephrostomy (PCN) tube or performing ureteroscopic procedures. 10 The purpose of the treatment is to diminish maternal pain, to prevent renal dysfunction and urinary tract infection and to decrease obstetric complications.…”
Section: Discussionmentioning
confidence: 99%
“…Placing nephrostomy tube in pregnancy has similar complications. 12,16,17 In the study of Parulkar et al 4 20 all types of stones with varying compositions can be fragmented into relatively small particles which can be easily eliminated. 21 Holmium laser lithotripters compared with pneumatic lithotripters, produce weak shock waves with minimal tissue penetration, thus theoretically limiting the risk of fetal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Stothers and Lee reported that microscopic hematuria is not evident in 25% of patients with diagnosed calculi. 6 Parulkar et al diagnosed lithiasis in 40 of 66 pregnancies with hematuria 11 and concluded that microscopic hematuria is not discriminatory for diagnosing calculi, and despite being a frequent sign, it is not specific.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound sensitivity for the diagnosis of urinary lithiasis varies between 34% 12 and 98%. 6 Parulkar et al demonstrated a sensitivity of 95.2% 11 for diagnosis of middle ureter lithiasis.…”
mentioning
confidence: 99%